2020
DOI: 10.3221/igf-esis.54.11
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mechanical behavior of friction stir welded joints of AA3003 aluminum alloy

Abstract: Friction stir welding (FSW) is an extremely complex process because it depends on the intrinsic and extrinsic factors of the material under consideration. The purpose of the present work is to formulate a set of recommendations concerning the choice of the different factors that are likely to influence the quality of the FSW joint and to find a mathematical model that allows predicting the mechanical behavior of the junction. An experimental design was therefore used to highlight the effect of the welding para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Investigating the butt FSWed joints of plates made of 3003-H24 alloy (Table 4), Kasman and Ozan [348] reported that at a WS of 50 mm/min, tunnel-type defects with large size appeared in joints welded with the TRS of 500 and 1000 rpm. The tunnel-type defects also occurred under WS of 80 mm/min and TRS of 500 and 800 rpm.…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the butt FSWed joints of plates made of 3003-H24 alloy (Table 4), Kasman and Ozan [348] reported that at a WS of 50 mm/min, tunnel-type defects with large size appeared in joints welded with the TRS of 500 and 1000 rpm. The tunnel-type defects also occurred under WS of 80 mm/min and TRS of 500 and 800 rpm.…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
“…Kasman and Ozan [348] studied the influence of welding process on the structural properties of the butt FSWed joints of plates made of 3003-H24 alloy. They found that the highest ultimate tensile strength among all the welded joints equal to 128 MPa was obtained under 50 mm/min WS and 800 rpm TRS.…”
Section: Mechanical Properties Hardnessmentioning
confidence: 99%
“…The FSW joints of 3003 alloy (Table 10), studied by Chekalil et al [412], were obtained using a tool with a flat shoulder with a diameter of 19.5 mm and a conical pin with a diameter varying from 6.8 to 5 mm and a length of 1.7 mm. The effect of the tool geometry on the joint properties was not studied.…”
Section: Tool Shoulder and Pin Geometrymentioning
confidence: 99%
“…For the FSW joints of components made of 3003 alloys (Table 6), Chekalil et al [412] reported that the joint mechanical properties were affected in the order of the TRS, the WS, and the tool tilt angle. The best mechanical properties of a welded joint were obtained under a TRS of 1423.9 rpm, a WS of 400 mm/min, and a tool tilt angle of 1.28 • .…”
mentioning
confidence: 99%
“…When regression and ANN were compared, it was discovered that ANN is much more accurate and robust than regression models. Chekilil et al [28] made a quadratic regression model to predict yield strength, yield strength strain, UTS, ultimate tensile strength strain, rupture strength, and elongation. Their model performed with a 95% confidence level.…”
Section: Introductionmentioning
confidence: 99%